Verba doctoris : la fecundidad educativa de las palabras del maestro - Martínez, Enrique (Sapientia, 2015)
In today’s educational world, pedagogical trends have been mired in what might be called «forgotten master», because it becomes unintelligible when there is no truth to impart. Education then becomes a construction by the student of a world of subjective and changing meanings, stimulates the teacher only. Against this, we find the teaching of St. Thomas Aquinas, Doctor Humanitatis, who reminds us that the teacher’s words, doctoris verba, are communicative truth already known. Only founded on this principle can be returned to the word education rightful fertility, so necessary to the perfection of man and society. This article presents a reflection on the place of the true word in the education of men, showing how human life is not meant only to express in words, but to be fruitful in the word education is presented.